Comparative genomic hybridization analysis of benign and invasive male breast neoplasms - Ojopi, EPB; Cavalli, L. R.; Cavalieri, LMB; Squire, J. A.; Rogatto, Silvia Regina [UNESP] (Elsevier B.V., 2002)
Comparative genomic hybridization (CGH) analysis was performed for the identification of chromosomal imbalances in two benign gynecomastias and one malignant breast carcinoma derived from patients with male breast disease and compared with cytogenetic analysis in two of the three cases. CGH analysis demonstrated overrepresentation of 8q in all three cases. One case of gynecomastia presented gain of 1p34.3similar topter. 11p14similar toq12. and 17p11.2similar toqter, and loss of 1q41similar toqter and 4q33similar toqter. The other gynecomastia presented del(1)(q41) as detected by both cytogenetic and CGH analysis. CGH analysis of the invasive ductal carcinoma confirmed a gain of 17p11.2similar toqter previously detected by cytogenetic analysis. These regions showed some similarity in their pattern of imbalance to the chromosomal alterations described in female and male breast cancer. (C) 2002 Elsevier B.V. All rights reserved.